THE POSITION OF THE REGULATION HEAD OF THE NUSANTARA CAPITAL AUTHORITY IN THE LEGISLATION SYSTEM - Probojati Bayu Herlambang; Syofyan Hadi (Fakultas Hukum Universitas Kadiri, 2024)
ABSTRACTThis study aims to determine and understand the position of the regulationof the Nusantara Capital Authority in the legislation system. The research methodused is a legal research method with a type of normative legal research in which theapproach used is a statute approach and a conceptual approach. The legal materialsused are primary, secondary, and tertiary legal materials. The results of this studyindicate that the position of the regulation of the Head of the Nusantara CapitalAuthority is equivalent to regional regulations. This is because: (1) The Head of theNusantara Capital Authority has a ministerial level position only in the proceduralaspect of his appointment, while in terms of forming regulations he has the positionof a regional head. (2) In terms of the authority to make rules, the Nusantara CapitalAuthority as a special regional unit at the provincial level has the authority ofattribution in terms of regulating (regelendad) the process of implementing thespecial regional government of the Nusantara Capital (3) Seeing that the positionof the Head of the Authority is the head of a special regional government, the legalproducts issued by the Head of the Nusantara Capital Authority are at the same levelas